Privacy 2.0. (29th April 2015) - Papathanassopoulos, Stylianos
We live in the era of change. In this world, privacy is not a static concept, but instead has a dynamic component. Overall, it becomes clear that the public and private are not defined in the same manner as in the past and as in the actual world, while our personal information has become a commodity that can raise our visibility in the social media driven world.